Upaya Meningkatkan Kemampuan Memahami Gagasan dan Fakta dalam Teks Eksposisi dengan Menerapkan Metode Discovery Learning - I Gede Gita Wiastra; I Wayan Agus Wiratama (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
Learning to understand ideas and facts in an exposition text of one of the materials taught in class VIII C of the State Junior High School 2 Tabanan. Based on the results of the initial research, it was found that students had difficulty in distinguishing ideas and facts in the exposition text. Students seem to pay less attention to the teacher's explanation and are busy doing other activities while the learning process is in progress. The learning process in the classroom takes place in one direction without involving students to ask questions, find out, and learn. In addition, the activities of ideas and facts in the exposition text are too book and theoretical so that learning does not seem to be able to encourage students to actively think to solve problems. This study aims to describe theability to understand ideas and facts in theexposition text of class VIII C students of StateJunior High School 2 Tabanan in the 2021/2022 academic year before and before applying the discovery learning method. Data collection methods used, namely the observation method and the test method. The observation method used to obtain data about student attitudes and behavior. The test method used to determine the ability to understand the ideas and facts in the exposition text. The data analysis method used is descriptive analysis method. Based on the data analysis, the results showed that the average value of students in the pre-cycle was 64.87, then in the first cycle it increased to 70.00 with the percentage increase from the pre-cycle to the first cycle of 8.91%. Furthermore, the average value of the class in the second cycle increased to 82.05 with the percentage increase from the first cycle to the second cycle of 18.21%. Thus, if it is rejected by the action hypothesis, the ability to understand and fact in the exposition text by applying the discovery learning Wacana - Volume XXII Edisi Oktober 2022 P a g e 57method of class VIII C students of State Junior HighSchool 2 Tabanan in the 2021/2022 academic year will increase.